Penerapan Model Problem Based Learning untuk Meningkatkan Pemahaman dan Penghayatan Nilai Kasih Kristus pada Peserta Didik Kelas X SMA Negeri 1 Kahaungu Eti, Sumba Timur - Santri Ferbistina Dor; Gregorius Daru Wijoyoko (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This classroom action research aims to improve students’ understanding and appreciation of the values of Jesus’ love through the implementation of the Problem-Based Learning (PBL) model among Grade 10 students at SMA Negeri 1 Kahaungu Eti, East Sumba. The study was motivated by the reality that most Catholic students in this school had never received formal Catholic Religious Education in previous levels, resulting in a limited cognitive grasp of faith without a corresponding manifestation in loving actions. The research was conducted in two cycles following the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, reflective questionnaires, and documentation. The findings reveal that the use of PBL enhanced students’ active participation in learning and fostered reflective attitudes toward their lived experiences. Students demonstrated a deeper understanding of Jesus’ love and applied it in social relationships at school, such as cooperation, mutual help, and respect for diversity. Therefore, the Problem-Based Learning model proved effective in developing the cognitive, affective, and practical dimensions of faith among Catholic students within a multireligious educational environment.